1976
DOI: 10.1097/00000658-197601000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor and Natural Course of Breast Cancer

Abstract: The tumors from approximately 50% of patients with breast cancer contained estrogen receptor (ER). ER appeared more often and at higher levels in the tumors of postmenopausal women. Eleven out of 12 patients who had multiple ER assays from various metastatic sites showed no significant discrepancies in ER values. ER level appears to decrease as the duration of metastatic cancer increase. Patients with ER in the tumor more frequently have bone metastases than those without ER. Visceral metastases occurred more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
1

Year Published

1977
1977
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 5 publications
0
16
1
1
Order By: Relevance
“…In Mexican patients studied, the lymphocytic infiltration was not as frequent. It is accepted that ER levels in breast cancer tumors of postmenopausal women are higher than the values of ER obtained in premenopausal patients [21], probably due to the partial saturation of ER originating from different sources. Our studies show a correlation between age of the patients and ER levels; an inverse relation in PgR values was found.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In Mexican patients studied, the lymphocytic infiltration was not as frequent. It is accepted that ER levels in breast cancer tumors of postmenopausal women are higher than the values of ER obtained in premenopausal patients [21], probably due to the partial saturation of ER originating from different sources. Our studies show a correlation between age of the patients and ER levels; an inverse relation in PgR values was found.…”
Section: Discussionmentioning
confidence: 87%
“…The premenopausal patients with ER respond to the endocrine treatment in 30-50% of the cases, whereas in postmenopausal the response rate increases to 60-70% due to the higher levels of free receptors [22,21]. When the menstrual state is not considered, the response to the endocrine treatment is 34% in patients with PgR+ [23] and indicates that premenopausal patients with PgR+ could be candidates for endocrine treatment, since various studies have demonstrated that PgR+ is more important than the ER+ value for the election of the endocrine treatment to be estrogen dependent [17].…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have suggested that ER-positive tumours are more likely to recur in the bone and ERnegative ones in the viscera and the brain (Singhakowinta et al, 1976;Stewart et al, 1981;Clark et al, 1987 first recurrence is highly statistically significant in terms of the median concentrations of ER and PR in relation to the site of the first recurrence. The higher the concentrations of ER and PR, the more likely it is that the first recurrence will be in bone, whereas the lower the concentrations are, the higher the possibility of visceral metastases.…”
Section: Discussionmentioning
confidence: 99%
“…While the incidence of ER and PR+ patients were higher over the age of 50 in some studies (Balleine et al, 1999), Pourzand and coworkers (2011) reported younger women had more likely PR+ tumors. Hormone receptors may alter survival, and induce better response to therapy in receptor positive patients (Singhakowinta et al, 1976;Kohil et al, 1985). The absence of relation between receptor status and pattern of metastasis may be linked with unknown factors such as genetics and molecular mechanisms among Iranian patients.…”
Section: 937 Metastasis and Survival In Iranian Breast Cancer Patientsmentioning
confidence: 99%